Konsep Transaksi di Restoran Masakan Padang dalam Ekonomi Syariah: Restoran Sederhana Masakan Padang Buah Batu Kota Bandung - Bahri, Yasir; Suryaman, Maman (Ikatan Da'i Indonesia, 2024)
There are so many people who do not know the basic laws of eating first and then making transactions, especially at the Padang Cuisine Restaurant in Buah Batu Bandung City, it is very common for people to make transactions at the end rather than at the beginning. Even though the transaction can be categorized as haram if the customer or consumer does not know what the original price of the goods he buys. However, the transaction can be categorized as legitimate if the customer or consumer knows from the price he bought. In this study, researchers aim to find out how the concept of transactions in the perspective of sharia economy, also to find out whether the padang cuisine restaurant has used sharia economic transactions or not, and to find out how the review of Islamic sharia with related transactions in Padang cuisine restaurants. The research method used by researchers is qualitative with literature analysis or literature studies with data collection techniques carried out by making observations, documentation, and literature or literature studies in accordance with the research target to be used as a source of information The result of this research is that the transaction will be haram, if the consumer or customer does not know the content of the price of the item, because some ulama' say it is haram for customers or consumers to eat first and then make a transaction and some other ulama' argue, that the transaction is said to be valid if the consumer or customer knows the price of the item. Researchers can conclude that the padang cuisine restaurant has used the Islamic economic system, and the transaction is legitimate with a note that customers must know the price of goods purchased or eaten, at least know the estimated price of goods to be purchased.